High Temperature Oxidation Behaviors of BaO/TiO2 Binary Oxide-Enhanced NiAl-Based Composites - Bo Li (MDPI AG, 2021)
High temperature lubricating composites have been widely used in aerospace and other high-tech industries. In the actual application process, high temperature oxidation resistance is a very importance parameter. In this paper, BaO/TiO2-enhanced NiAl-based composites were prepared by vacuum hot-press sintering. The oxidation resistance performance of the composites at 800 °C was investigated. The composites exhibited very good sintered compactness and only a few pores were present. Meanwhile, the composite had excellent oxidation resistance properties due to the formation of a dense Al2O3 layer which could prevent further oxidation of the internal substrate; its oxidation mechanism was mainly decided by the outward diffusion of Al and the inward diffusion of O. The addition of BaO/TiO2 introduced more boundaries and made the Kp value increase from 1.2 × 10−14 g2/cm4 s to 3.3 × 10−14 g2/cm4 s, leading to a slight reduction in the oxidation resistance performance of the composites—although it was still excellent.